2020
DOI: 10.1016/j.eats.2019.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Reconstruction Using a Ribbon-Like Graft With a C-Shaped Tibial Bone Tunnel

Abstract: According to recent anatomic studies, the anterior cruciate ligament (ACL) appears to be a flat, "ribbon-like" structure, with a thin, oval-shaped insertion on the femur and a C-shaped tibial insertion. According to this anatomy, we describe an ACL-reconstruction technique that aims to approximate this natural anatomy. The basic principle of this technique is not to use conventional round tunnels but create tunnel shapes that resemble more closely the original ACL insertion sites. Using either a rectangular qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…The tendon is put on a preparation board, and any fatty or muscular tissue is already removed. The round tendon part of the semiT then is dissected with a knife to half of its diameter (A, with a semiT allograft) and subsequently smoothed into a flat shape by blunt raspatorium at minimum pressure (B), as already described by Fink et al 30 Domnick et al 24 showed this does not affect the structural properties of the tissue. After that, the graft is folded once in 1/3 to 2/3 at an angle of about 45 (C) over a suture sling that is removed after preparation and kept in place with grasping forceps (D).…”
Section: Superficial MCL and Pol Reconstructionmentioning
confidence: 94%
See 1 more Smart Citation
“…The tendon is put on a preparation board, and any fatty or muscular tissue is already removed. The round tendon part of the semiT then is dissected with a knife to half of its diameter (A, with a semiT allograft) and subsequently smoothed into a flat shape by blunt raspatorium at minimum pressure (B), as already described by Fink et al 30 Domnick et al 24 showed this does not affect the structural properties of the tissue. After that, the graft is folded once in 1/3 to 2/3 at an angle of about 45 (C) over a suture sling that is removed after preparation and kept in place with grasping forceps (D).…”
Section: Superficial MCL and Pol Reconstructionmentioning
confidence: 94%
“…The round tendon part of the semiT then is dissected with a knife to half of its diameter (A, with a semiT allograft) and subsequently smoothed into a flat shape by blunt raspatorium at minimum pressure (B), as already described by Fink et al. 30 Domnick et al. 24 showed this does not affect the structural properties of the tissue.…”
Section: Introductionmentioning
confidence: 94%
“…In this technique, the tibial tunnel forms a round shape. Based on anatomical knowledge, it may be ideal to make the tibial tunnel into a rounded rectangle or C-shape [ 7 , 30 ]. The shape of the tibial bone tunnel has to be changed if the lateral anterior meniscus is damaged, and this would lead to poor clinical results due to the round bone tunnel.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Smigielski et al reported that the ACL, including its femoral and tibial insertions, appears to be flat and "ribbon-like" after the removal of the synovial membrane [6]. After this report, instead of double-bundle ACL reconstruction and the conventional single-bundle ACL reconstruction, new anatomical single-bundle techniques using a hamstring tendon (oval femoral tunnel [7] and rectangular femoral tunnel [8]) have been developed and reported. Observing the cross-sectional shape of the quadrupled hamstring harvested at surgery, we felt that it approximated an oval shape.…”
Section: Introductionmentioning
confidence: 99%
“…To better restore the anatomy of the native ACL attachment and fibers arrangement, several researchers have developed techniques that change the shape of the ACL bone tunnel into oval, rectangular, rounded-rectangular, or “C" shapes, with some satisfactory early clinical outcomes. 6 , 22 , 23 In this study, we used a flat-tunnel ACL reconstruction technique developed by Liu et al 20 and Zhang et al 47 , 49 Using this technique, the shape of the bone tunnel was adjusted to a rounded rectangle. It was assumed that, by adjusting the shape of the tibial tunnel, the rounded-rectangular tunnel (RRT) would be able to better mimic the flat anatomy of native tibial attachment and lower the risk of damaging the ARLM attachment.…”
mentioning
confidence: 99%